Vacuum deposited coatings on polyester film - Howells, D (2006)
The work contained in this thesis examines how the properties of polyester film substrates affect the structure and performance of thin coatings vacuum-deposited upon them, particularly with regards to their function as gas barriers for use in packaging. By modifying the surface of a PET film prior to deposition, with either oxygen or argon plasma, an increase in adhesion between the polymer and coating by 50% occurs for both aluminium and SiOₓ layers. A reduction in the density of pinhole defects is also observed after such treatment. A set of silicon oxide (SiOₓ) coatings, deposited using a novel PECVD method, that display excellent barrier to water vapour permeation, impressive mechanical properties and good adhesion to the base film, is studied. Water vapour transmission rates as low as 2 x 10⁻⁴g m⁻² day⁻¹ are reported for these thin films as a result of their thickness and structure, where the deposition of the coating in several layers prevents defects extending throughout the coating. A high level of carbon incorporated in these films makes them flexible with relatively high strain to failure and low stress. The properties of the SiOₓ coatings vary significantly depending on the substrate on which they are deposited. By tailoring the polyester film properties during manufacture, a wide range of substrates with differing properties is produced. The most relevant appear to be the surface thermal and mechanical properties. SiOₓ layers on heat stabilised PET (with or without an additional primer layer) and PEN outperform an equivalent coating on standard PET film by two orders of magnitude, in terms of gas barrier, and also possess superior mechanical properties. This is due to the enhanced thermal stability of the surfaces of these films as they undergo heating during deposition, as thermally induced motion of the chains at the surface of a plain PET film is thought to create defects. Substrate roughness is found to affect the morphology of deposited coatings but not the permeation of gas through them. The importance of substrate selection is illustrated by substituting PET with PEN, for example, where improvement in barrier is comparable to that achieved by coating a polymer film in the first place.